Fine needle aspiration cytology in diagnosis of cystic swelling of neck: a three year prospective study - Annapurna, P.; Pattnaik, Niharika (International Surgery Journal, 2022)
Background: Cystic lesion in the neck originates from lymph nodes, skin appendages, soft tissues, salivary gland or developmental anomalies of neck like branchial cleft. Present study has been designed to know the anatomical site of cystic swelling, dividing them in cystic, inflammatory, benign, and malignant groups. Methods: FNAC was done using 22 gauge needles. The aspirated material was smeared on the slide and stained with Hematoxylin and Eosin 31 (H and E), Papanicoloau staining and stained with May Grunwald Giemsa (MGG) stain. Wherever suspicion of tubercular pathology was there ZN stain was used. Results: Regarding distribution of organ involved in cystic swelling of neck, as per table 2, cystic swelling associated with thyroid was in 80 (40%) patients, cystic swelling associated with lymph node was in 86 (43%) patients, cystic swelling associated with salivary gland was in 20 (10%) patients, cystic swelling associated with soft tissue and miscellaneous was in 6 (3%) patients and non specific sample was seen in 4 (2 %) patients. Conclusions: From present study we can conclude that that mean age of the patients was 34.66±4.21 yrs and most of the patients were below 40 years of age and there was male predominance. In present study lymph node was most common organ with cystic swelling (43%) and thyroid (40%) was next to it. Salivary gland was third most common organ involved (10%). In our study Colloidal goitre was present in 38(19%) patients and tuberculosis was present in 42(21%) patients.